Optimalisasi Pengawasan Pembiayaan Mudharabah Berbasis Smart Monitoring System - Alfina Finky Ramadhani; Pungky Lela Saputri; Alfi Rohmatul Haniyah; Chintiya Nurafriani (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
Financing has a very important role for Islamic banks, namely contributing greatly to efforts to restore the national economy. In its distribution, weak supervision will become a gap for customers to default in financing. Therefore, the optimization of Financing Supervision Based on the Smart Monitoring System which makes it easier for Islamic banks to carry out the supervision process as an effort to maintain the continuity of Islamic banks must be realized. This research is research and development with ADDIE approach (Analyze, Design, Develop, Implement, and Evaluate). Research is limited to the design stage. This study uses descriptive writing and qualitative descriptive analysis methods. The data collected in this paper are primary data and secondary data. The purpose of this study is to develop a more practical and more efficient online smart system-based monitoring or monitoring system to ensure the suitability of the financing provided with existing procedures.